The problem asks to prove the identity
∑k=1n(k2−k+1)=31n(n2+2n)
using the principle of Mathematical Induction.
Step 1: Base Case (n = 1)
For n=1, the left-hand side (LHS) becomes:
∑k=11(k2−k+1)=12−1+1=1
The right-hand side (RHS) for n=1 is:
31×1×(12+2×1)=31×1×(1+2)=31×1×3=1
Since LHS = RHS for n=1, the base case holds.
Step 2: Inductive Hypothesis
Assume that the statement is true for some n=m. That is, assume:
∑k=1m(k2−k+1)=31m(m2+2m)
Step 3: Inductive Step
We need to prove that the statement holds for n=m+1, i.e.,
∑k=1m+1(k2−k+1)=31(m+1)((m+1)2+2(m+1))
Start with the left-hand side for n=m+1:
∑k=1m+1(k2−k+1)=∑k=1m(k2−k+1)+((m+1)2−(m+1)+1)
Using the inductive hypothesis:
=31m(m2+2m)+((m+1)2−(m+1)+1)
Simplify the expression for (m+1)2−(m+1)+1:
(m+1)2−(m+1)+1=m2+2m+1−m−1+1=m2+m+1
Thus, the equation becomes:
31m(m2+2m)+(m2+m+1)
Now, combine these terms. First, express the second part as a fraction with denominator 3:
=31m(m2+2m)+33(m2+m+1)
Combine the terms over the common denominator:
=31(m(m2+2m)+3(m2+m+1))
Simplify the expression inside the parentheses:
m(m2+2m)=m3+2m2
3(m2+m+1)=3m2+3m+3
Thus, we have:
=31(m3+2m2+3m2+3m+3)
=31(m3+5m2+3m+3)
This is the expanded form of:
31(m+1)((m+1)2+2(m+1))
Thus, the inductive step holds, and by the principle of mathematical induction, the identity is true for all n≥1.
Would you like more details or clarification on any step?
Here are 5 related questions for further practice:
- Prove the formula for the sum of the first n squares using induction.
- Prove the identity ∑k=1nk3=(2n(n+1))2 using mathematical induction.
- Show that 2n>n2 for all n≥5 using induction.
- Verify the sum of an arithmetic progression formula using induction.
- Use induction to prove that n!>2n for n≥4.
Tip: When proving by induction, always carefully check both the base case and the transition from the n=m to n=m+1 case.